2013
DOI: 10.1021/ja311416v
|View full text |Cite
|
Sign up to set email alerts
|

2-Bromopalmitate Analogues as Activity-Based Probes To Explore Palmitoyl Acyltransferases

Abstract: Reversible S-palmitoylation is an important post-translational modification that regulates the trafficking, localization, and activity of proteins. Cysteine-rich Asp-His-His-Cys (DHHC) domain-containing enzymes are evolutionarily conserved protein palmitoyl acyltransferases (PATs). The human genome encodes 23 DHHC-PATs that regulate diverse cellular functions. Although chemical probes and proteomic methods to detect palmitoylated protein substrates have been reported, no probes for direct detection of the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(82 citation statements)
references
References 32 publications
2
79
1
Order By: Relevance
“…We have synthesized analogues of 2-BP and cerulenin with an alkyne tail, which serve as bioorthogonal chemical reporters for covalently labeling and profiling PATs and autopalmitoylated proteins 22,23 . Through proteomic and biochemical studies, we have identified that the TEAD transcription factors are palmitoylated at evolutionarily conserved cysteine residues.…”
Section: Instroductionmentioning
confidence: 99%
“…We have synthesized analogues of 2-BP and cerulenin with an alkyne tail, which serve as bioorthogonal chemical reporters for covalently labeling and profiling PATs and autopalmitoylated proteins 22,23 . Through proteomic and biochemical studies, we have identified that the TEAD transcription factors are palmitoylated at evolutionarily conserved cysteine residues.…”
Section: Instroductionmentioning
confidence: 99%
“…Alkyne derivatives of 2-bromopalmitic acid (16C-BYA and 18C-BYA, Figure 4c) efficiently labeled DHHC-2, DHHC-3 and DHHC-4 proteins, but not their catalytically dead mutants, in live cells by forming stable irreversible adducts with the catalytic cysteine residues [62]. Additionally, mass spectrometry studies highlight the wide range of off-target effects of 2-bromopalmitic acid and its lack of specificity, as exemplified by labeling of reactive cysteines within palmitoylating and non-palmitoylating enzymes, acyl-CoA enzymes, and proteins that potentially undergo autoacylation or bind palmitoylCoA.…”
Section: Tools To Probe Fatty Acylation Of Proteinsmentioning
confidence: 99%
“…Concomitantly, 2-BP-treated BMDCs lost the ability to produce high levels of the pro-inflammatory cytokines IL-6 and TNFα in response to Pam 3 CSK 4 and lipomannan, which are microbe-based ligands specifically detected by TLR2 ( Figure 3B). Since prolonged exposure to 2-BP can result in off-target effects and cellular toxicity [55,56], we also employed Sendai virus, a TLR-independent activator of cytoplasmic RIG-I-like receptors, as a control [57][58][59][60][61]. Sendai virus induced high levels of IL-6 and TNFα secretion even in the presence of 2-BP (although TNFα was partially affected), indicating that the effects of 2-BP were largely specific to the TLR2 pathway ( Figure 3B).…”
Section: Palmitoylation Of Cd86 and Tlr2 Can Be Increased By Specificmentioning
confidence: 99%